A critical role of transcription factor YY1 in rheumatoid arthritis by regulation of interleukin-6. (February 2017) - Lin, Jinpiao; He, Yujue; Chen, Junmin; Zeng, Zhiyong; Yang, Bin; Ou, Qishui
Abstract: Previous studies have revealed a critical role of YY1, a "Yin Yang" transcription factor, in cancer development and progression. However, whether YY1 has any role in rheumatoid arthritis (RA) remains unknown. This study aims to explore the potential role of YY1 in RA pathogenesis. In this study, we found that YY1 was over-expressed in RA patients and CIA mice. Blocking of YY1 action with YY1 shRNA lentivirus ameliorated disease progression in CIA mice. We further analyzed the signaling pathway involved by ingenuity pathway analysis (IPA), results showed IL-6 signaling and JAK/Stat signaling pathway was significantly inhibited by LV-YY1-shRNA treatment. Moreover, we observed that blocking of YY1 reduced IL-6 production and downregulated Th17 population. Finally, we showed YY1 positively regulated IL-6 transcription by binding to the promoter region of the IL-6 gene. In conclusion, YY1 plays a critical role in promoting IL-6 transcription in RA which contribute to the inflammation of RA via stimulation of Th17 differentiation. Thus, YY1 is likely a key molecule involved in the inflammation process of RA. Targeting of YY1 may be a novel therapeutic strategy for RA. Highlights: Identified YY1 was over-expressed in RA patients and CIA mice firstly. Blocking YY1 ameliorated disease progression in CIA mice. Blocking YY1 inhibited IL-6 signaling and JAK/Stat signaling pathway. YY1 regulated Th17 and Treg balance via IL-6 signaling pathway in RA. YY1 positively regulated IL-6 transcription by binding to the promoter region of the IL-6.